Assessing the Retail Environments of Licensed and Unlicensed Cannabis Dispensaries: Adapting the Marijuana Retail Surveillance Tool to Inform Cannabis Regulation in Los Angeles County. Issue 4 (July 2021) - Nicholas, Will; Washburn, Faith; Lee, Grace; Loprieno, Daniele; Greenwell, Lisa; Berg, Carla
Abstract : Context: After statewide legalization of recreational cannabis in California, the Los Angeles (LA) County Board of Supervisors requested a health equity impact assessment to inform its decisions on whether and how to regulate cannabis dispensaries in unincorporated areas of LA County. Objective: As part of this assessment, the LA County Department of Public Health compared the retail environments of licensed and unlicensed cannabis dispensaries in different parts of the county, using the Marijuana Retail Surveillance Tool (MRST), a validated instrument piloted in Colorado and Washington. Design: Two waves of observational surveys were conducted, one comparing licensed and unlicensed dispensaries within and near unincorporated areas of LA County and another comparing licensed dispensaries across LA County in areas with varying levels of health advantage according to a neighborhood index measuring social determinants of health. Main Outcome Measures: Dispensaries were compared on measures of product types, promotional activities, security measures, regulatory compliance, and neighborhood context. Results: Unlicensed dispensaries were more likely than licensed dispensaries to sell products in packaging designed to be attractive to children (71.8% vs 10.8%, P < .001) and in non–child-resistant packaging (98.9% vs 15.6%, P < .001) and were more likely allow on-site consumption (60.9% vs 0%, P < .001). Licensed dispensaries showed high compliance with regulations, regardless of whether they were in areas of high or low health advantage. Conclusions: The study points to the importance of efforts to eliminate illicit businesses as part of an overall strategy for regulating cannabis. It also demonstrates that the MRST is a flexible tool for regulatory surveillance and for continuing to study the relationships between cannabis retail environments and potential risks to public health.